ANALYSIS OF THE LAPAK HIJAU BUSINESS MODEL IN THE SALE OF FURNITURE GOODS THROUGH THE E-COMMERCE PLATFORM - Fakhriyyah , Alma Nisa; Wiranata, Ade Davy (Informatika, Universitas Jenderal Soedirman, 2024)
The problems researched concern how Lapak Hijau can optimize its operations, increase customer accessibility, and maximize profits through the integration of second-hand furniture sales in an e-commerce environment including business model analysis in the context of second-hand furniture sales through an e-commerce platform. Lapak Hijau is a company engaged in buying used goods from various sources, including hotels, restaurants, and factories and reselling them at a higher price. This research aims to analyze Lapak Hijau's business model in the sale of used furniture through an e-commerce platform focusing on business model changes that allow integrating the sale of used furniture through an e-commerce platform. The research method combines business model analysis with a literature review on e-commerce and stock management to identify the optimal strategy for Lapak Hijau in integrating second-hand furniture sales in an e-commerce environment. The results of this research provide an in-depth insight into effective business strategies for Lapak Hijau in taking on the challenges and opportunities in the e-commerce era. The conclusion of this research will outline practical recommendations for Lapak Hijau and similar businesses in enhancing their success and growth in the digital environment.